Implementasi Gamifikasi dalam Pengembangan Media Pembelajaran Logika Matematika Diskrit Berbasis Game 3D - Wildan Sulistiono; Faisal Reza Pradhana; Triana Harmini (LPPM Universitas Putera Batam, 2025)
Education is a fundamental aspect in the development of human resources, especially in the field of computer science. One of the core subjects is Discrete Mathematics, yet many students struggle to grasp its concepts, particularly in logic. Based on observations and student grades from the Informatics Engineering Department at Darussalam Gontor University, it is evident that comprehension levels remain low. This study aims to develop a 3D game-based learning media using a gamification method. The software was developed using the Software Development Life Cycle (SDLC) waterfall model and implemented using Unity with 3D interactive control. The application was evaluated through questionnaires to content experts, media experts, and users. Validation results indicate the application is feasible as an alternative learning medium and can enhance students’ understanding and motivation in learning.